SPECT and fluorescence imaging of vulnerable atherosclerotic plaque with a vascular cell adhesion molecule 1 single-chain antibody fragment. (November 2016) - Liu, Chunbao; Zhang, Xiao; Song, Yiling; Wang, Yichun; Zhang, Fengzhen; Zhang, Yingying; Zhang, Yongxue; Lan, Xiaoli
Abstract: Background and aims: Early detection and evaluation of vulnerable atherosclerotic plaque are important for risk stratification and timely intervention, and vascular cell adhesion molecule 1 (VCAM1) assists in adhesion and recruitment of inflammatory cells to vulnerable lesions. We labeled a single-chain variable fragment (scFv) of VCAM1 with 99m technetium ( 99m Tc) and fluorescent markers to investigate its potential utility in detecting vulnerable plaques in animal models of atherosclerosis. Methods: We labeled VCAM1 scFv with 99m Tc and cyanine5 (CY5) and evaluated the probes on apolipoprotein E gene-deficient mice and New Zealand White rabbits with induced atherosclerosis. Histopathology and Western blot examinations confirmed atherosclerotic plaque and VCAM1 expression in the aortas. In vivo biodistribution of 99m Tc-scFv-VCAM1 was studied. Abdominal organs of mice were removed after CY5-scFv-VCAM1 administration for aortic fluorescence imaging. Rabbits SPECT imaging of 99m Tc-scFv-VCAM1 was performed and autoradiography (ARG) of the aortas was checked to confirm the tracer uptake. Results: The radiochemical purity of 99m Tc-scFv-VCAM1 was 98.72± 1.04% ( n = 5) and its specific activity was 7.8 MBq/μg. Biodistribution study indicated predominant probe clearance by kidneys. In fluorescence imaging, stronger signal from CY5-scFv-VCAM1 in the aorta was observed in atherosclerotic mice than that in controls. SPECT imaging with 99m Tc-scFv-VCAM1 showed tracer uptake in the abdominal aorta and the aortic arch of atherosclerotic animals. ARG confirmed tracer uptake in the aortas of atherosclerotic rabbits, with higher uptake ratios of aortic arch/descending aorta in experimental animals (4.45 ± 0.63, n = 5) than controls (1.12 ± 0.15, n = 5; p < 0.05). Conclusions: SPECT and fluorescence imaging results showed the feasibility and effectiveness of detecting vulnerable plaque with scFv of VCAM1, indicating its potential for early diagnosis and evaluation of atherosclerosis. Highlights: Atherosclerosis plaques were induced in mice and rabbits models. Imaging probes of VCAM1 scFv were prepared with radionuclide and fluorescent dye. Fluorescence and SPECT imaging confirmed the detection of atherosclerosis plaque in vivo .